Digital Games as Safe Places: The Case of Animal Crossing - Ferreira Cátia; Ganito Carla; Gonçalves Soraia (Open Cultural Studies)
Digital games have become a popular cultural pastime and a profitable media industry, with an average player age of 32. During the lockdown years, the many facets of digital games came to light, particularly their capacity to encourage the development of safe spaces for interaction and communities. Games that encourage creativity and content creation, like Second Life, Animal Crossing, and Minecraft, for example, give users a variety of safe spaces to express themselves and grow creatively. The article addresses the function of video games as safe spaces using a mixed-methods approach, emphasizing the role played during the pandemic and using Animal Crossing as an example. Three primary techniques for gathering data were an online survey, netnography, and document analysis. Through the Animal Crossing: New Horizons case study, we were able to confirm that players do, in fact, view the game as more than just a way to pass the time. They make expressive and proactive use of it, deriving immense pleasure from producing and disseminating content that is uniquely personalized for them. It is a tool for escapism and provides a feeling of belonging to players who agree that the New Horizons Fan Community is a united, helpful, caring, and generous community.